Criterios Sostenibles Aplicados a la Vivienda de Autoconstrucción - Rojas Romero, John Jairo (Universidad Antonio Nariño, 2022)
The degree work entitled "Sustainable criteria applied to self-construction housing". Case Study: the city of Bogotá and its surroundings, arises from the academy and from the author's interest in questioning how the development of sustainable criteria in self-built homes can influence processes of improvement of the informal habitat, integrating its time, the urban, economic, social and environmental aspects. It also seeks to make contributions that may be useful in decisionmaking and development of planning policies or urban instruments, due to the lack of sustainable criteria for housing in Colombian regulations, with which it is intended to contribute by incorporating some measures that help in strategic policies and preparation of national plans or subsequent management instruments.